The Campylobacter jejuni RacRS two-component system activates the glutamate synthesis by directly upregulating γ-glutamyltranspeptidase (GGT) - van der Stel, Anne-Xander; van Mourik, Andries; Lanniewski, Pawel; van der Putten, Jos P.; Jagusztyn-Krynicka, Elżbieta K.; Wosten, Marc M. (Frontiers in Microbiology, 2015)
The highly conserved enzyme γ-glutamyltranspeptidase (GGT) plays an important role in metabolism of glutathione and glutamine. Yet, the regulation of ggt transcription in prokaryotes is poorly understood. In the human pathogen Campylobacter jejuni, GGT is important as it contributes to persistent colonization of the gut. Here we show that the GGT activity in C. jejuni is dependent on a functional RacRS (reduced ability to colonize) two-component system. Electrophoretic mobility shift and luciferase reporter assays indicate that the response regulator RacR binds to a promoter region 80 bp upstream of the ggt transcriptional start site, which contains a recently identified RacR DNA binding consensus sequence. RacR needs to be phosphorylated to activate the transcription of the ggt gene, which is the case under low oxygen conditions in presence of alternative electron acceptors. A functional GGT and RacR are needed to allow C. jejuni to grow optimally on glutamine as sole carbon source under RacR inducing conditions. However, when additional carbon sources are present C. jejuni is capable of utilizing glutamine independently of GGT. RacR is the first prokaryotic transcription factor known to directly upregulate both the cytoplasmic (glutamine-2-oxoglutarate aminotransferase (GOGAT)) as well as the periplasmic (GGT) production of glutamate.